Answers

2016-05-06T11:49:18+05:30
Let the speed of the boat be 'x' kmph.
then the speed in downstream will be= (x+3)kmph
the speed in upstream will be= (x-3)kmph
now we have, 6(x+3)=12(x-3)
6x+18=12x-36
18+36=12x+6x
54=18x
x=54/18
x=3
::speed of the river is 3 kmph
0
ans is wrong buddy check plz
oops
yes ,, u answered correctly
my answer was wrong
2016-05-06T14:40:32+05:30
Let the speed of the boat be 'X' km/h.
Then the speed in downstream = (x+3)km/h
                speed in upstream = (x-3)km/h
As per question
                        6(x+3)=12(x-3)
=6x+18=12x-36
=18+36=12x-6x(transpose)
6x=54
x=54/6
x=9
::speed of the river is 9 km/h
0
plz mark my aswer as brainlest
answer*